Physical and chemical properties of cultivation area that enhance the growth of Tegillarca granosa (Linnaeus, 1758) - Md Joni, Amirul Azuan (2017)
Due to the uncertain trend of cockle production in Malaysia, it causes this industry to be at stake. Continuous and sustainable cockle supply is imperative in order to fulfil public demand. To achieve a consistent and sustainable cockle production, solid understanding on the cockle habitat is highly imperative. Therefore it is imperative to identify and investigate the environmental condition that acts as supporting or limiting factors for cockle cultivation. The objectives of the study is to investigate the physicochemical properties of sediment and water column at proposed cultivation area, to estimate the growth and survival rate of cockle at the proposed cultivation site, and lastly to established and select the best cultivation sites at Kongkong Laut by comparing with the reference area (Sungai Ayam). Screening of the physico-chemicals properties of water from the study sites was done from January until December 2015 and sediment was in December 2014 until March 2015. For water parameter analysis, negative correlation was found between water turbidity level and dissolved oxygen level (r= -0.572, P<0.01), the water pH level (r= -0.611, P<0.01) and positive correlation was found between the turbidity level and the water temperature (r= 0.511, P<0.01). This is because, higher turbidity level was due to high levels of total suspended solids within a water column, thus increase water temperatures and lead to decrease dissolved oxygen (DO) levels. A weak positive correlation was found between dissolved oxygen level with water pH level (r= 0.436, P<0.01), indicating factor that influence dissolved oxygen level within the Kongkong Laut estuary was not only due to temperature, but also due to the decomposition of organic substances as it also is a common process within an estuaries area. A significant positive correlation was found be-tween the level of nitrate concentration in water and phosphate concentration (r= 0.778, P<0.01), thus proves that both nitrate and phosphate concentration within the water might derived from the palm oil farm which located at the upper part of the estuaries. For sediment physico-chemical analysis, moderately negative correlation was found between sedimentary organic matter and pH level (r= -0.660, P<0.01), indicating that the accumulation of organic matter in lower pH level within the sediment as high organic matter availability within the sediment lead to higher organic matter decomposition activity within the area. A significant positive correlation was found between sedimentary salinity and electroconductivity level (r= 0.737, P<0.01), signify that the concentration of salt that is trapped within the sediment might become the major influence that effects the level of sedimentary electroconductivity within Kongkong Laut estuaries. The determination of suitable cockle plot was mainly focused on two main factor. Based on the present of the mudflat and wild cockle within the sampling stations, KK1 (within Zone 1), KK7 (within Zone 2) and KK8 (within Zone was selected for further plot study. Among all of the three plot study, it is aware that Plot KK7 has the highest average cockle’s growth increment (2.70 ± 0.32 mm per month), followed by KK8 (2.09 ± 0.27 mm per month) and KK1 (2.05 ± 0.16 mm per month) respectively. It is revealed that there was a significant positive moderate correlation between the salinity level and the cockle’s growth rate (p<0.05, r=0.65), suggesting that salinity is might be the main reason for higher cockle’s growth increment within Plot KK7. Among all of the three plot study, it is aware that Plot KK7 has the highest average cockle’s survival rate (92 % per month) followed by KK8 (87%) and KK1 (73 % per month) respectively along the monitoring period from August to December 2015). The result suggested that turbidity might be the main reason that affecting cockles’ survival within all of the plots as a high level of turbidity within a prolonged period of time have the potential to negatively affect cockle’s survival within a habitat drastically. While, salinity was found to be the main reason that promotes cockle’s growth within Kongkong Laut area as lower salinity condition leads to restrict cockle’s feeding activity. As for that, KK7 was found to be the most optimal site for cockle cultivation activity in Kongkong Laut estuaries area due to highest cockle growth and survival rate that has been recorded. Comparison of water parameter between KK7 and reference site in Sungai Ayam shows that there was significant difference (p<0.05) in turbidity, salinity and dissolved oxygen, with Sungai Ayam shows a higher trend compare to KK7 station. While, comparison of sediment physicochemical parameter shows that there was significant difference (p<0.05) in all of the measured parameter (sand, silt, clay, organic matter, pH, salinity, electroconductivity). Although there were significant different of several parameters between reference site and KK7 station, the water and sediment physicochemical range of KK7 is still within the optimal range for cockle cultivation activity, thus explain highest cockle growth and survival rate of plot KK7 compare to plot KK1 and KK8.